براءات الاختراع في الوطن العربي (the status of patents in the Arab World: an evaluation introductory) - Khalifa, Othman Omran; Nasser, Youcef (2019)
يتوجه العالم أكثر مما مضى نحو الاقتصاد القائم على المعرفة؛ حيث تشكل التكنولوجيا أحد عناصر المعرفة التي باتت في خدمة التنمية الاقتصادية والاجتماعية. ويشهد العالم حالياً تغيرات جذرية في سوق التكنولوجيا، مثل تعاظم أهمية المدخلات التكنولوجية في عمليات الإنتاج والخدمات. تبين الإحصاءات الواردة ضمن هذا العمل التقييمي تدني تعداد براءات الاختراع المطلوبة والممنوحة في بلدان الوطن العربي، وهذا مقارنة بدول مثل: ماليزيا وتركيا وجنوب إفريقيا وإيران التي كانت وضعيتها الاقتصادية والتعليمية إلى وقت قريب تتشابه أو تتطابق مع وضعية الدول العربية الحالية، لكن السؤال الذي يفرض نفسه بقوة: ما سبب هذا التدني الكبير في براءات الاختراع في الوطن العربي؟ فهل من إجابات حاسمات؟ The innovation and scientific creativity becomes a necessity for any progress and development. Societies cannot be grow and settle unless self-sufficiency is achieved in their local production, which stems from their scientific creations and their innovative innovations which vary in economic, educational, literary, cultural, administrative, industrial, medical, agricultural and other fields. At a time when the major industrialized countries have maintained their growing pace in registering large numbers of patents, the Arab nation has only been on the list for decades. In this paper we present the status of patents in the Arab world, as they represent an important indicator for measuring the work of research and development and technological innovation at the level of industrial establishments as well as universities and research centers. The patent can also be used as an indicator for comparison between industrial establishments and countries.